Influence of Mitochondrial Substrates and Cofactors on Tear Liquid Production and Components in Occupational Dry Eye Syndrome - N. K. Mazina; S. G. Anisimova (Антибиотики и Химиотерапия)
Hypoxia and oxidative stress are especially distinguished among the links in the pathogenesis of the dry eye syndrome, however tear replacement therapy dominates in the treatment of this disease, while tear stimulants and antihypoxants are still not as popular.The aim of the study is to investigate the effect of a preparation containing mitochondrial substrate and oxidation cofactors on the production and composition of lacrimal fluid in occupational dry eye syndrome.Materials and Methods: 124 patients (office managers and welders) with occupational dry eye syndrome were randomized into 4 symmetric comparison groups. The patients in two of the groups received a medication containing succinic acid, riboxin, nicotinamide, and riboflavin; while the other two groups received placebo. The treatment regimen in all groups consisted of 3 cycles of 2 tablets 2 times per day for 25 days with 1 month break. Schirmer test was used to assess tear production, Norn's test — to control tear stability. Tear composition (proteins, glucose, cholesterine, triglycerides, iron, and calcium levels) was also checked. The tests and tear components assessment were undertaken before and after every cycle, as well as 6 and 12 months after the end of treatment.Results: initially, tear production and stability of the tear film were reduced by 1.5–2.0 times in both welders and office workers; the content of protein, triglycerides, cholesterol, iron, and calcium was reduced by 2–3 times. As the pharmacodynamic effects of the drug were summarized during treatment, tear production and tear film strength increased by the end of the 3rd cycle, the content of protein, glucose, triglycerides, cholesterol, iron, and calcium in the lacrimal fluid increased; positive changes prevailed among office workers.Conclusion: mitochondrial substrates and cofactors improve tear liquid production, properties and composition of the tear film in the case of occupational dry eye syndrome.